Without Lies or Deception': Oracular Claims to Truth in the Epistle to Titus* - Harrill, J. Albert (New Testament studies, 2017)
The claim to communicate the divine without lies or deception' appears both in the Epistle to Titus and in contemporaneous debates about the truth value of oracles, but not because of any direct literary borrowings from an original source. The Epistle to Titus exemplifies a trend in the second century that created from oracular one-liners a literary discourse about divination, which defended traditional religious knowledge against the rise of unauthorised agents. Shared responses to contemporary phenomena best explain the parallels - and, for example, the quotation of a pagan oracle in the letter, All Cretans are liars' (Titus 1.12).